Diagnostic information in GP referral letters to a memory clinic: a retrospective cohort study - Demi Ronner; Dorien Oostra; Jurgen Claassen; Edo Richard; Marieke Perry (BJGP Open)
Background: Dementia diagnostics can often be performed in primary care, yet older people with memory complaints are frequently referred to memory clinics (MCs). Aim: To compare diagnostic information in GP referral letters of patients with and without an eventual dementia diagnosis. Design & setting: Retrospective cohort study in a Dutch academic MC. Method: We collected electronic health record (EHR) data of consecutive patients aged ≥65 years referred by their GP between 2016 and 2020. EHR data included patient characteristics, diagnostic information in referral letters, ancillary investigations performed at the MC, and established diagnoses. We performed χ2 tests to compare groups. Results: Of 651 patients included, the average age was 78.0 years (standard deviation 6.8) and 348 (53.5%) were diagnosed with dementia. Most people with dementia were diagnosed without ancillary investigations (n = 235/348, 67.5%). In GP referral letters of people with dementia compared with people without dementia, a collateral history, any physical examination, a differential diagnosis including dementia, a Mini-Mental State Examination score, interference with daily functioning, and decline from previous levels of functioning were mentioned more often. Furthermore, the more diagnostic criteria mentioned in the referral letter, the more often dementia was diagnosed at the MC (no criteria: 35.4%; one criterion: 47.3%; two criteria: 53.4%; three criteria: 69.9%; and four or five criteria: 83.3%). Conclusion: GPs often correctly mention diagnostic information and dementia criteria in referral letters of people with dementia, and they are often diagnosed without ancillary investigations. This suggests that referral is often unnecessary, and GPs can be empowered to diagnose dementia themselves.